ASP.NET Core 2 and Vue.js : full stack web development with Vue, Vuex, and ASP.NET Core 2.0 - Ratcliffe, Stuart (Packt Publishing, 2018)
Microsoft have recently expanded their suite of SPA project templates to include a Vue.js based template that includes all the tooling required to build modern production ready applications out of the box. In this book, we'll leverage some of the more powerful Vue.js features with ASP.NET core backend to build modern web apps.